Geology still matters – Unconventional petroleum system disappointments and failures - Barry Katz; Ling Gao; Jessica Little; Yushi Russell Zhao (Unconventional Resources, 2021)
Machine learning and factory drilling approaches have increased efficiency and improved the commerciality in many tight plays. However, not all the original resource estimates and potential opportunities have, been confirmed by the drill-bit. Although some of the commercial disappointments have been a result of policy decisions, more often they are due to partial or complete failure of the unconventional petroleum system and/or the hydrocarbon phase encountered.Studies have demonstrated that not all mudrocks are organic-rich, contain the appropriate kerogen type, have achieved the appropriate level of thermal maturity, have suitable unconventional reservoir properties, are able to retain hydrocarbons, or have the necessary resource density to be a viable tight rock target. An overview of six shale plays in this study (the Longmaxi Shale of China, the Silurian shales of eastern Europe, the Cambay Shale of India, the Barnett Shale in northeast Texas, the Eagle Ford Shale of South Texas, and the Waltman Shale of Wyoming) represent the diversity of potential geologic problems.It becomes apparent that, just as in the case of conventional exploration, successful unconventional exploration and development requires a full assessment of the petroleum system. Absence or limited effectiveness of one or more elements (i.e., source rock presence, quality, and thermal maturity, reservoir presence and quality, and retention) of the petroleum system is a primary driver for mismatch between resource expectations and results.